The Little House books. Volume two - Wilder, Laura Ingalls, 1867-1957 (Library of America, 2012)
Follows the adventures of the Ingalls family from the time they find a livable homestead in De Smet, Dakota Territory, through the courtship and marriage of Laura and Almanzo.